A comparison of aquatic and semiaquatic Heteroptera (Hemiptera) inhabiting natural habitats and experimental mesocosms at the University of Mississippi Field Station. Issue 1 (2nd January 2020) - Pintar, Matthew R.; Resetarits, William J.
Abstract: Aquatic and semiaquatic Heteroptera (Hemiptera) in the infraorders Gerromorpha and Nepomorpha were collected from the University of Mississippi Field Station (UMFS) in north-central Mississippi from May 2014 until August 2019. UMFS encompasses over 200 ponds, springs, wetlands, and streams in the headwaters of the Little Tallahatchie River. We collected insects from mesocosm experiments and natural water bodies in order to survey and document the aquatic and semiaquatic Heteroptera of UMFS. A total of 20, 304 individuals were collected representing 43 species in 20 genera and 10 families (Belostomatidae, Corixidae, Gerridae, Hebridae, Hydrometridae, Mesoveliidae, Naucoridae, Nepidae, Notonectidae, Veliidae). We compare mesocosms and natural water bodies in terms of species present and their abundances, and we also provide notes on the abundance, distribution, and habitats of some species, with new state records for three species.